2014
DOI: 10.1016/j.parkreldis.2014.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Clinician versus machine: Reliability and responsiveness of motor endpoints in Parkinson's disease

Abstract: Background Enhancing the reliability and responsiveness of motor assessments required to demonstrate therapeutic efficacy is a priority for Parkinson's disease (PD) clinical trials. The objective of this study is to determine the reliability and responsiveness of a portable kinematic system for quantifying PD motor deficits as compared to clinical ratings. Methods Eighteen PD patients with subthalamic nucleus deep brain stimulation (DBS) performed three tasks for evaluating of resting tremor, postural tremor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 39 publications
1
101
1
1
Order By: Relevance
“…These differences may have contributed to what represents only a moderate correlation with MDS-UPDRS-III scores. As subjective scales are limited in accuracy and reliability [1], a moderate correlation suggests a tablet-based application may be capable of detecting differences in motor function beyond those probed by the MDS-UPDRS-III. In fact, the test-retest reliability for both medication states was higher than that reported for the MDS-UPDRS-III (0.60–0.71) [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences may have contributed to what represents only a moderate correlation with MDS-UPDRS-III scores. As subjective scales are limited in accuracy and reliability [1], a moderate correlation suggests a tablet-based application may be capable of detecting differences in motor function beyond those probed by the MDS-UPDRS-III. In fact, the test-retest reliability for both medication states was higher than that reported for the MDS-UPDRS-III (0.60–0.71) [26].…”
Section: Discussionmentioning
confidence: 99%
“…PD-specific motor scales also have limitations in logistic deployment, reliability, and spatial resolution [1, 2, 27]. These shortcomings may lower the signal-to-noise ratio in the measurement of relevant endpoints in clinical trials, lowering the ability of finding statistically significant differences between interventions of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, early studies suggest that a smartphone application in Parkinson disease can differentiate those with the disease from those without, be used to predict disease severity as assessed by traditional measures, and detect pharmacological effects of approved therapies [31]. In addition, where evidence of value has been generated [32-36], the US Food and Drug Administration has cleared some digital biomarkers for use [37, 38]. …”
Section: Opportunity For Digital Biomarkersmentioning
confidence: 99%
“…Studies have shown that this technique is feasible and can offer similar benefits to that of in-person evaluations [92,93]. Although many of these devices compare favourably with the "gold standard" of assessments of motor function, the MDS-UPDRS, and can provide greater test-retest reliability and sensitivity to change than conventional clinical ratings [94], there are current limitations to such approaches. Some aspects of assessment such as rigidity are extremely difficult to assess remotely and these devices remain to be validated in large population of patients with PD.…”
Section: Minimising Variability / Error In Assessing Endpointsmentioning
confidence: 99%